Determinant Factors of Profitability in Fintech Lending Companies in Indonesia from 2019 to 2022 Using Principal Component Analysis (PCA) - Nomba, Aditya Novanto; Rikumahu, Brady (PT FORMOSA CENDEKIA GLOBAL, 2024)
This reserach examines factors influencing the profitability of Fintech lending companies in Indonesia. A purposive sampling method was employed to select 45 companies annually. The data for this research are cross-sectional, comprising the years 2019, 2020, 2021, and 2022. The methods in this research are Principal Component Analysis (PCA) and multiple linear regression. Findings reveal that current ratio, cash ratio, working capital turnover, debt to assets ratio, short-term debt ratio, equity multiplier, total assets turnover, fixed assets turnover, tangible assets ratio, and effective tax rate significant determinants of profitability for Fintech lending companies in Indonesia. This reserach can help Fintech lending companies improve their profitability.